قدرات التسويق الإلكتروني: تطوير سلم قياس متعدد الأبعاد: E-Marketing Capabilities: Developing a Multidimensional Measurment Scale - لرادي سفيان; بربار نورالدين (Journal of North African Economies, 2025)
This study aims to propose a reliable measurement scale to the e-marketing capabilities by employing capabilities theory, resources-based strategy theory and e-marketing components approach. After using qualitative study through interviews and quantitative study through a largescale survey, the study generates a valid and reliable items distributed over four dimensions of emarketing capabilities: 1) Social media marketing capabilities/online advertising capabilities, 2) Web presence capabilities, 3) mobile marketing capabilities, 4) E-mail marketing capabilities.